Термодесорбційні дослідження бромованого вугілля СКН - Veselovska, K. I.; Veselovskyi, V. L.; Zakharova, T. M.; Byeda, A. A.; Diyuk, V. E.; Ishchenko, E. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2015)
It was studied the thermal stability of the grafted groups and the state of the surface of the initial and modified activated carbons (ACs) samples by Temperature-programmed desorption mass spectrometry (TPD-MS) and thermogravimetric analysis (TGA). According to TPD-MS studies, grafted bromine, regardless of its nature and modification temperature, is desorbed just as molecules HBr, while nitrogen-containing group – as nitrogen-containing ions NH2+, CH2NH2+ and CH3CHNH2+. It was shown that the gas-phase bromination of ACs is an effective method of modification and leads to obtaining samples with up to 2.5 mmol/g of chemically grafted bromine. It was found that the active surface bromines is substituted with nitrogen-containing groups in amounts up to 1.1 mmol/g at the liquid-phase amination of brominated samples.